Thermal response self-ceramic fireproof coating and preparation method thereof

By designing a chemical and physical cross-linking network in a composite system, a dense ceramic layer is formed at high temperatures, solving the problem of insufficient fire resistance of cable fire-retardant coatings under continuous heat attack and achieving high-strength fire protection.

CN121045903APending Publication Date: 2025-12-02STATE GRID ANHUI ELECTRIC POWER CO LTD ELECTRIC POWER SCI RES INST

Patent Information

Application Number
CN202510958354.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-12-02

Smart Images

  • Figure CN121045903A_ABST
    Figure CN121045903A_ABST
Patent Text Reader

Abstract

The invention provides a thermal response self-ceramization fireproof coating and a preparation method thereof. The thermal response self-ceramization fireproof coating is prepared from the following raw materials in parts by mass: 3 to 10 parts of acrylic monomer, 3 to 10 parts of organic sulfonate, 1 to 4 parts of silane coupling agent, 0.5 to 3 parts of silicate ester, 4 to 6 parts of ceramic precursor, 3 to 6 parts of fluxing agent and 0.05 to 0.4 part of initiator. The fluxing agent comprises a component A and a component B, the component A is one of boric oxide, zinc borate or low-melting-point glass powder, and the component B is one of phosphorus pentoxide and ammonium polyphosphate. The silane coupling agent can be copolymerized with an acrylic monomer to construct a C-C main chain, the C-C main chain and silicate ester are subjected to hydrolytic condensation to form a Si-O-Si three-dimensional network, a chemical cross-linked skeleton is formed, and the chemical cross-linked skeleton can generate silicon dioxide at high temperature to participate in a ceramization reaction; the ceramic precursor and silicate ester can form a strong physical cross-linking effect, so that the fireproof coating with a chemical and physical double-cross-linked network can be formed, and the fireproof coating has excellent mechanical property and machinability at normal temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fire-retardant coating technology, specifically to a thermally responsive self-ceramicizing fire-retardant coating and its preparation method. Background Technology

[0002] Cables, as the core carrier of modern power transmission and signal communication, have a wide range of applications and are of paramount importance. Because cable insulation and sheathing materials are mostly made of flammable polymers such as polyethylene and polyvinyl chloride, they are highly susceptible to fire and release highly toxic fumes when ignited by a short circuit or external fire source, posing significant safety risks. Fire-retardant coatings, as a key means of cable surface protection, must possess strong adhesion at room temperature, high-temperature thermal stability, and fire resistance integrity under extreme conditions. However, existing cable fire-retardant coatings still have significant performance deficiencies under complex operating conditions.

[0003] Chinese invention patent document CN114015261A discloses an inorganic water-resistant, zero-VOC ceramicized expansion fireproof coating, comprising the following components: 20-30 parts potassium silicate, 10-20 parts lithium silicate, 3-6 parts sodium methylsilicate, 6-10 parts ceramic precursor, 8-15 parts flame retardant, 2-3 parts lithium magnesium silicate, 0.5-1.5 parts dispersant, 0.3-0.5 parts defoamer, and 20-30 parts water. This document relies on high-temperature foaming to form core-shell spherical structures; however, magnesium hydroxide can decompose at high temperatures, causing the core-shell spherical structures to undergo oxidative degradation under sustained high temperatures, resulting in insufficient fire resistance time. Summary of the Invention

[0004] The technical problem to be solved by this invention is how to improve the long-term protection of cables by fire-retardant coatings under continuous heat attack.

[0005] The present invention solves the above-mentioned technical problems through the following technical means:

[0006] The first aspect of this invention provides a thermally responsive self-ceramicized fire-retardant coating, comprising the following raw materials in parts by weight: 3-10 parts acrylic monomer, 3-10 parts organic sulfonate, 1-4 parts silane coupling agent, 0.5-3 parts silicate ester, 4-6 parts ceramic precursor, 3-6 parts flux, and 0.05-0.4 parts initiator; wherein the flux comprises components A and B, wherein component A is one of boron oxide, zinc borate, or low-melting-point glass powder, and component B is one of phosphorus pentoxide or ammonium polyphosphate.

[0007] Beneficial effects: The acrylic monomer of this invention has good flexibility and a large number of active groups, which can improve the mechanical properties and strong adhesion of fire-retardant coatings; the organic sulfonate exerts its intrinsic flame-retardant effect and induces the formation of phase-separated micro-nano structures, thereby generating a mechanical interlocking effect with the cable, further improving the interfacial adhesion of the coating; the silane coupling agent can copolymerize with the acrylic monomer to construct the CC backbone and hydrolyze and condense with silicate esters to form a Si-O-Si three-dimensional network, forming a chemical cross-linked skeleton. The chemical cross-linked skeleton can generate silica at high temperature to participate in the ceramization reaction; the ceramic precursor can form a strong physical cross-linking effect with silicate esters, which helps to form a fire-retardant coating with both chemical and physical cross-linked networks, giving it excellent mechanical properties and processability at room temperature.

[0008] The ceramic precursor possesses both high strength and thermal stability, enabling it to undergo a eutectic reaction with hydrolyzed silicates at high temperatures to form a ceramic structure. The flux, an AB compound system, achieves efficient ceramicization over a wide temperature range. After being subjected to high-temperature flame erosion, it can rapidly transform into a high-strength, high-heat-resistant hard ceramic barrier layer, providing fireproofing, insulation, heat insulation, and shock resistance. This ensures that the fire-retardant coating can withstand continuous fire or external impact, creating a fire-retardant coating with high strength and efficient fire protection.

[0009] Preferably, the mass ratio of component A to component B is 1:0.9-1.5.

[0010] Preferably, the acrylic monomer is hydroxyethyl acrylate or alkyl acrylate phosphate.

[0011] Preferably, the organic sulfonate is one of sodium vinyl sulfonate, sodium allyl sulfonate, or sodium methpropylene sulfonate.

[0012] Preferably, the silane coupling agent is one of KH570, A151, A171, A172 or A174.

[0013] Preferably, the silicate ester is one of methyl methyl silicate, tetraethyl orthosilicate, or tetrapropoxysilane.

[0014] Preferably, the ceramic precursor includes one or more of montmorillonite, mica, kaolin, zinc oxide, boron nitride, aluminum nitride, hollow glass microspheres, clay, wollastonite, titanium dioxide, talc, alumina, zirconium oxide, titanium oxide, silicon carbide, and tungsten carbide.

[0015] Preferably, the initiator is one of potassium persulfate, sodium persulfate, and ammonium persulfate.

[0016] A second aspect of the present invention provides a method for preparing the above-mentioned heat-responsive self-ceramicized fire-retardant coating, comprising the following steps:

[0017] S1 involves mixing and dispersing acrylic monomers, organic sulfonates, silane coupling agents, and water, then adding an initiator to initiate a polymerization reaction. After the reaction is complete, silicate esters are added to obtain a coating matrix containing an organosilicon precursor.

[0018] S2 disperses the ceramic precursor and flux in water to obtain a suspension, adds the suspension to a coating matrix containing an organosilicon precursor, stirs and evaporates to obtain a thermally responsive self-ceramicized fireproof coating.

[0019] Beneficial effects: This invention rationally designs a thermally responsive self-ceramicized fire-retardant coating with a phase-separated micro-nano structure through simple free radical copolymerization, hydrolysis condensation and composite technology. It can form interfacial hydrogen bonds and mechanical interlocking with cables, exhibiting strong interfacial adhesion. The fire-retardant coating has a chemical and physical dual cross-linked network and has excellent mechanical properties and processability at room temperature.

[0020] Preferably, the polymerization reaction is carried out at a temperature of 50-75°C for 5-18 hours.

[0021] Beneficial effects: The fire-retardant coating of the present invention has the advantages of excellent corrosion resistance, high flame retardant efficiency and low moisture absorption. At the same time, it belongs to the water-based coating system, does not contain VOC, is non-toxic and harmless, has a simple production process, and adopts a scraping process for application, which is quick and safe to apply and is suitable for large-scale production. Attached Figure Description

[0022] Figure 1 This is a scanning electron microscope image of the thermally responsive self-ceramicized fire-retardant coating of Example 1;

[0023] Figure 2 The graph shows the surface change of the thermally responsive self-ceramicized fire-retardant coating of Example 1 at 1100°C over time. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0026] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.

[0027] Example 1

[0028] This embodiment provides a thermally responsive self-ceramicizing fire-retardant coating and its preparation method, as detailed below:

[0029] The thermally responsive self-ceramicized fireproof coating comprises the following raw materials in parts by weight: 6 parts hydroxyethyl acrylate, 7 parts sodium allyl sulfonate, 3 parts KH570 silane coupling agent, 1 part tetraethyl orthosilicate, 4 parts ceramic precursor, 4 parts flux, and 0.2 parts potassium persulfate.

[0030] The ceramic precursors are montmorillonite and mica, with a mass ratio of montmorillonite to mica of 1:1.

[0031] The flux is zinc borate and ammonium polyphosphate, with a mass ratio of zinc borate to ammonium polyphosphate of 1:1.

[0032] The preparation method of the thermally responsive self-ceramicized fire-retardant coating is as follows:

[0033] In step S1, 6 parts of hydroxyethyl acrylate, 7 parts of sodium allyl sulfonate, 3 parts of KH570 silane coupling agent, and 40 parts of deionized water were sequentially added to a three-necked flask. The raw materials were thoroughly mixed using a mechanical stirrer, and then heated to 65°C using an oil bath heater. During this process, 0.2 parts of potassium persulfate were slowly added to the three-necked flask, and the polymerization reaction was stirred for 6 hours. Afterward, 1 part of tetraethyl orthosilicate was added to the three-necked flask, and the reaction was stirred for 5 hours to obtain a coating matrix containing an organosilicon precursor.

[0034] S2 disperses 4 parts of ceramic precursor and 4 parts of flux in 20 parts of deionized water, prepares a uniform suspension by high-speed stirring, and adds the suspension to a coating matrix containing organosilicon precursor under high-speed stirring. After the raw materials are mixed evenly, the deionized water is concentrated to 45 parts by rotary evaporation to obtain a thermally responsive self-ceramicized fireproof coating.

[0035] The scanning electron microscope (SEM) characterization image of the thermally responsive self-ceramicized fire-retardant coating prepared in this embodiment is shown below. Figure 1 As shown, from Figure 1 As can be seen, the thermally responsive self-ceramicized fire-retardant coating possesses a phase-separated micro / nano structure. The surface change of the thermally responsive self-ceramicized fire-retardant coating prepared in this embodiment at 1100℃ over time is shown in the figure below. Figure 2 As shown, from Figure 2 As can be seen, the fire-retardant coating exhibits significant thermal response self-ceramization behavior. Within two minutes, the base resin of the fire-retardant coating rapidly pyrolyzes to form a black carbon layer; after four minutes of heating, the ceramic precursor and flux undergo a melt-crystallization synergistic effect under high temperature to form a dense white ceramic layer.

[0036] Example 2

[0037] This embodiment provides a thermally responsive self-ceramicizing fire-retardant coating and its preparation method, as detailed below:

[0038] The thermally responsive self-ceramicized fireproof coating comprises the following raw materials in parts by weight: 10 parts alkyl acrylate phosphate, 9 parts sodium vinyl sulfonate, 2 parts A151 silane coupling agent, 1 part methyl methacrylate, 6 parts ceramic precursor, 5 parts flux, and 0.3 parts sodium persulfate.

[0039] The ceramic precursors are kaolin and zinc oxide, with a mass ratio of kaolin to zinc oxide of 1:1.

[0040] The flux is zinc borate and phosphorus pentoxide, with a mass ratio of zinc borate to phosphorus pentoxide of 1:1.

[0041] The preparation method of the thermally responsive self-ceramicized fire-retardant coating is as follows:

[0042] In step S1, 10 parts of alkyl acrylate phosphate, 9 parts of sodium vinyl sulfonate, 2 parts of A151 silane coupling agent, and 50 parts of deionized water were sequentially added to a three-necked flask. The raw materials were thoroughly mixed using a mechanical stirrer, and then heated to 70°C using an oil bath heater. During this process, 0.3 parts of sodium persulfate were slowly added to the three-necked flask, and the polymerization reaction was stirred for 8 hours. Afterward, 1 part of methyl methyl silicate was added to the three-necked flask, and the reaction was stirred for 6 hours to obtain a coating matrix containing an organosilicon precursor.

[0043] S2 disperses 6 parts of ceramic precursor and 5 parts of flux in 30 parts of deionized water, prepares a uniform suspension by high-speed stirring, and adds the suspension to a coating matrix containing organosilicon precursor under high-speed stirring. After the raw materials are mixed evenly, the deionized water is concentrated to 55 parts by rotary evaporation to obtain a thermally responsive self-ceramicized fireproof coating.

[0044] Example 3

[0045] This embodiment provides a thermally responsive self-ceramicizing fire-retardant coating and its preparation method, as detailed below:

[0046] The thermally responsive self-ceramicized fireproof coating comprises the following raw materials in parts by weight: 5.5 parts alkyl acrylate phosphate, 5 parts sodium methacrylate sulfonate, 1.6 parts A171 silane coupling agent, 0.8 parts tetrapropoxysilane, 4.5 parts ceramic precursor, 4 parts flux, and 0.15 parts ammonium persulfate.

[0047] The ceramic precursors are montmorillonite and boron nitride, with a mass ratio of montmorillonite to boron nitride of 1:1.2.

[0048] The flux consists of hollow glass microspheres and ammonium polyphosphate, with a mass ratio of hollow glass microspheres to ammonium polyphosphate of 1:1.1.

[0049] The preparation method of the thermally responsive self-ceramicized fire-retardant coating is as follows:

[0050] In step S1, 5.5 parts of alkyl acrylate phosphate, 5 parts of sodium methacrylate sulfonate, 1.6 parts of A171 silane coupling agent, and 30 parts of deionized water were sequentially added to a three-necked flask. The raw materials were thoroughly mixed using a mechanical stirrer, and then heated to 68°C using an oil bath heater. During this process, 0.15 parts of ammonium persulfate were slowly added to the three-necked flask, and the polymerization reaction was stirred for 7 hours. Afterward, 0.8 parts of tetrapropoxysilane were added to the three-necked flask, and the reaction was stirred for 5 hours to obtain a coating matrix containing an organosilicon precursor.

[0051] S2 disperses 4.5 parts of ceramic precursor and 4 parts of flux in 20 parts of deionized water, prepares a uniform suspension by high-speed stirring, and adds the suspension to a coating matrix containing organosilicon precursor under high-speed stirring. After the raw materials are mixed evenly, the deionized water is concentrated to 35 parts by rotary evaporation to obtain a thermally responsive self-ceramicized fireproof coating.

[0052] Example 4

[0053] This embodiment provides a thermally responsive self-ceramicizing fire-retardant coating and its preparation method, as detailed below:

[0054] The heat-responsive self-ceramicized fire-retardant coating comprises the following raw materials in parts by weight:

[0055] 6 parts hydroxyethyl acrylate, 9 parts sodium methacrylate sulfonate, 4 parts A172 silane coupling agent, 1.5 parts tetraethyl orthosilicate, 4 parts wollastonite, 3.5 parts flux, and 0.35 parts ammonium persulfate.

[0056] The flux consists of zinc borate and ammonium polyphosphate, with a mass ratio of zinc borate to ammonium polyphosphate of 1:1.

[0057] The preparation method of the thermally responsive self-ceramicized fire-retardant coating is as follows:

[0058] In step S1, 6 parts of hydroxyethyl acrylate, 9 parts of sodium methacrylate sulfonate, 4 parts of A172 silane coupling agent, and 50 parts of deionized water were sequentially added to a three-necked flask. The raw materials were thoroughly mixed using a mechanical stirrer, and then heated to 65°C using an oil bath heater. During this process, 0.35 parts of ammonium persulfate were slowly added to the three-necked flask, and the polymerization reaction was stirred for 6 hours. Afterward, 1.5 parts of tetraethyl orthosilicate were added to the three-necked flask, and the reaction was stirred for 6 hours to obtain a coating matrix containing an organosilicon precursor.

[0059] S2 disperses 4 parts wollastonite and 3.5 parts flux in 30 parts deionized water and prepares a uniform suspension by high-speed stirring. The suspension is then added to a coating matrix containing an organosilicon precursor under high-speed stirring. After the raw materials are mixed evenly, the deionized water is concentrated to 50 parts by rotary evaporation to obtain a thermally responsive self-ceramicized fireproof coating.

[0060] Comparative Example 1

[0061] The difference between this comparative example and Example 1 is that no KH570 silane coupling agent and tetraethyl orthosilicate were added in this comparative example; otherwise, they are the same as in Example 1.

[0062] Comparative Example 2

[0063] The difference between this comparative example and Example 1 is that the mass ratio of zinc borate to ammonium polyphosphate in the flux of this comparative example is 1:2, while all other aspects are the same as in Example 1.

[0064] Comparative Example 3

[0065] The difference between this comparative example and Example 1 is that the flux in this comparative example is zinc borate, while everything else is the same as in Example 1.

[0066] Comparative Example 4

[0067] The difference between this comparative example and Example 1 is that the flux in this comparative example is ammonium polyphosphate, while everything else is the same as in Example 1.

[0068] Experimental Example

[0069] The thermally responsive self-ceramicized fire-retardant coatings of Examples 1-4 and Comparative Examples 1-4 were tested using the following methods:

[0070] Clean steel plates were selected as substrates. The fire-retardant coatings of Examples 1-4 and Comparative Examples 1-4 were evenly and smoothly applied to the substrates. After being left at room temperature for 2 hours, they were placed in a forced-air drying oven at 60°C for 6 hours. Different thicknesses were controlled according to different test items, and the thickness standard referred to GB / T 1727-2021. Three samples were coated for each group of samples as templates.

[0071] The performance of the fire-retardant coatings of Examples 1-4 and Comparative Examples 1-4 was tested in accordance with relevant standards. The test standards and performance indicators are shown in Table 1.

[0072] Table 1

[0073]

[0074]

[0075] As shown in Table 1, Comparative Example 1 failed to form a chemical cross-linked network due to the absence of silane coupling agent and silicate ester. This cross-linked structure imparts cohesiveness to the coating, directly affecting its adhesion grade. Furthermore, tetraethyl orthosilicate hydrolyzes to generate SiO2 sol, which undergoes a eutectic reaction with the ceramic precursor at high temperatures. The absence of this component leads to incomplete ceramization, manifested in reduced flexural strength of the ceramic layer formed at 900-1000℃.

[0076] In Comparative Example 2, since the mass ratio of zinc borate to ammonium polyphosphate is 1:2, adding too much ammonium polyphosphate causes it to decompose and produce gases such as NH3 and H2O. When the gas content is too high, micropore defects are formed in the ceramic layer, reducing the structural density and significantly reducing the bending strength at 900-1000℃.

[0077] Comparative Examples 3 and 4, containing only one component of the flux, with zinc borate having a melting temperature of 980℃, cannot effectively wet the ceramic precursor particles in the 800-900℃ range, leading to incomplete sintering and a significant decrease in flame retardancy and ceramicization efficiency. Ammonium polyphosphate decomposes into polymetaphosphate at 300-500℃, which can promote low-temperature melting, but above 800℃, the PO network is prone to depolymerization, causing structural collapse of the high-temperature ceramic layer. Therefore, the single-component flux significantly reduces flame retardancy and ceramicization efficiency.

[0078] This invention, through chemical and physical dual cross-linking network design and compounding with AB flux, enables the fire-retardant coating to have excellent mechanical properties and processability at room temperature, ensuring that the fire-retardant coating can withstand continuous fire or external impact, thus constructing a fire-retardant coating with high strength and high efficiency fire protection.

[0079] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A thermally responsive self-ceramicizing fire-retardant coating, characterized in that, The raw materials include the following components by weight: 3-10 parts acrylic monomer, 3-10 parts organic sulfonate, 1-4 parts silane coupling agent, 0.5-3 parts silicate ester, 4-6 parts ceramic precursor, 3-6 parts flux, and 0.05-0.4 parts initiator. The flux comprises components A and B, wherein component A is one of boron oxide, zinc borate, or low-melting-point glass powder, and component B is one of phosphorus pentoxide or ammonium polyphosphate.

2. The thermally responsive self-ceramicizing fire-retardant coating according to claim 1, characterized in that, The mass ratio of component A to component B is 1:0.9-1.

5.

3. The thermally responsive self-ceramicizing fire-retardant coating according to claim 1, characterized in that, The acrylic monomer is hydroxyethyl acrylate or alkyl acrylate phosphate.

4. The thermally responsive self-ceramicizing fire-retardant coating according to claim 1, characterized in that, The organic sulfonate is one of sodium vinyl sulfonate, sodium allyl sulfonate, or sodium methpropylene sulfonate.

5. The thermally responsive self-ceramicizing fire-retardant coating according to claim 1, characterized in that, The silane coupling agent is one of KH570, A151, A171, A172 or A174.

6. The thermally responsive self-ceramicizing fire-retardant coating according to claim 1, characterized in that, The silicate ester is one of methyl methyl silicate, tetraethyl orthosilicate, or tetrapropoxysilane.

7. The thermally responsive self-ceramicizing fire-retardant coating according to claim 1, characterized in that, The ceramic precursor includes one or more of the following: montmorillonite, mica, kaolin, zinc oxide, boron nitride, aluminum nitride, hollow glass microspheres, clay, wollastonite, titanium dioxide, talc, alumina, zirconium oxide, titanium oxide, silicon carbide, and tungsten carbide.

8. The thermally responsive self-ceramicizing fire-retardant coating according to claim 1, characterized in that, The initiator is one of potassium persulfate, sodium persulfate, and ammonium persulfate.

9. The method for preparing a thermally responsive self-ceramicized fire-retardant coating as described in any one of claims 1-8, characterized in that, Includes the following steps: S1 involves mixing and dispersing acrylic monomers, organic sulfonates, silane coupling agents, and water, then adding an initiator to initiate a polymerization reaction. After the reaction is complete, silicate esters are added to obtain a coating matrix containing an organosilicon precursor. S2 disperses the ceramic precursor and flux in water to obtain a suspension, adds the suspension to a coating matrix containing an organosilicon precursor, stirs and evaporates to obtain a thermally responsive self-ceramicized fireproof coating.

10. The method for preparing a thermally responsive self-ceramicized fire-retardant coating according to claim 9, characterized in that, The polymerization reaction is carried out at a temperature of 50-75℃ for 5-18 hours.

Citation Information

Patent Citations

  • Inorganic water-resistant zero-VOC ceramic intumescent fireproof coating as well as preparation method and application thereof

    CN114015261A

Cited By

  • Water-based inorganic nano ceramic heat-insulating coating and preparation method thereof

    CN122127818A

  • Polyacrylic acid-based fireproof coating and preparation method thereof, and organic silicon composite polyacrylic acid flame-retardant material and preparation method thereof

    CN122127849A